2013
DOI: 10.1002/gcc.22061
|View full text |Cite
|
Sign up to set email alerts
|

Multiple pilomatricomas with somatic CTNNB1 mutations in children with constitutive mismatch repair deficiency

Abstract: Constitutional mismatch repair deficiency (CMMR-D) due to biallelic germline mutations in one of four mismatch repair genes causes a childhood cancer syndrome characterized by a broad tumor spectrum including hematological malignancies, and brain and Lynch syndrome-associated tumors. Herein, we report three children who had in addition to CMMR-D-associated malignancies multiple pilomatricomas. These are benign skin tumors of hair matrical differentiation frequently associated with somatic activating mutations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 35 publications
3
48
0
1
Order By: Relevance
“…Heterogeneous descriptions have been provided for the cutaneous phenotype of CMMRD10 28 and this study suggests that common dermatological features at presentation combine widespread or segmental CALMs and hypopigmented macules. Congenital naevi are less common, as well as pilomatricomas, rare non-malignant skin tumours unrelated to NF1 29. As previously reported,28 30 cutaneous abnormalities were absent in rare cases in this series.…”
Section: Discussionsupporting
confidence: 77%
“…Heterogeneous descriptions have been provided for the cutaneous phenotype of CMMRD10 28 and this study suggests that common dermatological features at presentation combine widespread or segmental CALMs and hypopigmented macules. Congenital naevi are less common, as well as pilomatricomas, rare non-malignant skin tumours unrelated to NF1 29. As previously reported,28 30 cutaneous abnormalities were absent in rare cases in this series.…”
Section: Discussionsupporting
confidence: 77%
“…In support of this notion, it was shown that distinct pilomatricomas occurring in a single CMMRD patient resulted from different activating CTNNB1 (ß-Catenin gene) mutations. This suggests that certain genes may be targeted repeatedly by independent somatic mutational events in CMMRD patients [14]. Accordingly, the constitutional polymerase proofreading defect may explain the occurrence of these features in our patient.…”
Section: Discussionmentioning
confidence: 80%
“…In two patients with genetically confirmed CMMRD syndrome, multiple pilomatricomas were reported. The authors proposed that the presence of multiple pilomatricomas that is seen very rarely in otherwise healthy individuals should raise a suspicion for an underlying MMR repair defect when observed in a paediatric cancer patient 28. Of note, there may also be an association of multiple pilomatricomas with MUTYH-associated polyposis,29 a polyposis syndrome that has certain phenotypical and patho-mechanistic overlap with CMMRD since both recessively inherited tumour predisposition syndromes are caused by DNA repair defects leading to attenuated polyposis although usually in different age groups.…”
Section: The Clinical Phenotype Of Cmmrd As Deduced From the Known Casesmentioning
confidence: 99%